Роль свиты разведчиц медоносных пчел в передаче информации о пространственном положении корма - Левченко, И.А.; Шалимов, И.И. (Вестник зоологии, 1968)
It is established by the method of photo- and cinema-registration of individually labelled bees that the suite of a prospecting bee consists of bees of various age but a number of foraging bees (older than 22 days) is the greatest. The main body of bees (78 p. c.) finds a feeding area in accordance with information contained in the dances of the prospecting bee, in suite of which they were. A small number of bees (12.5 p. c.) finds a feeding-area which does not correspond to the co-ordinates shown by the prospecting bee, in suite of which they were. The time for searching a feeding area for them is 3.7 times as much as that for the bees received correct information. Some bees (8.7 p. c.) find a feeding area without taking part in suites of pros-pecting bees. When feeding aromatized food a number of bees, that found a feeding area without participation in the suite, increases noticeably. A conclusion is made on existance of some methods for finding the sources of food by bees: a) a random search; b) a search by odour; c) a search according to the signals of prospecting bees' dances.